Direct and indirect effects of tree canopy facilitation in the recruitment of Mediterranean oaks - Caldeira, Maria C.; Ibáñez, Inés; Nogueira, Carla; Bugalho, Miguel N.; Lecomte, Xavier; Moreira, Andreia; Pereira, João S. (Journal of Applied Ecology, 2014)
* Tree recruitment in Mediterranean ecosystems is strongly limited at the seedling stage by drought. Increasing evidence shows the critical positive role of the canopy nurse effect on seedling survival which results from direct and indirect, positive and negative interactions between species. * Most studies, however, have only focused on the effects of tree canopy on water and light, ignoring other critical factors affecting seedling regeneration, such as canopy effects on high temperatures and the competing herb biomass. * Here, we evaluate how tree canopy cover and removal of herbs affect the survival and growth of seedlings of two dominant Mediterranean Quercus species during a 3-year study. We use an integrated model that combines several data sets to quantify and predict regeneration dynamics along environmental gradients of soil moisture, temperature and light. * Low soil moisture, increased soil temperature and herb biomass negatively affected seedling survival of both Quercus species. Seedling growth was positively associated with increasing soil moisture and light. * Although tree canopy cover directly facilitated seedling survival in both Quercus species, it also negatively affected herb biomass and thus indirectly facilitated the survival of Quercus suber, but not of Quercus ilex seedlings at low levels of soil moisture. * Overall, tree canopies increased seedling survival but not growth during the establishment phase, mainly by ameliorating the effects of low soil moisture and high temperatures. Tree canopy indirectly facilitated survival of Q. suber seedlings by negatively affecting the competing herb layer. * Synthesis and applications. To improve tree recruitment and conserve Mediterranean Quercus woodlands, the removal of herbs should be integrated into management plans for dry habitats. Interactions between abiotic and biotic factors may also effect the regeneration of these tree species. In particular, a healthy tree canopy will become important for providing conditions to facilitate seedling establishment if these habitats become drier and warmer, as predicted by some climate change scenarios.
Keywords: climate change; herb management; high temperatures; positive interactions; Quercus ilex; Quercus suber; tree recruitment

Hydraulic Lift in Cork Oak Trees in a Savannah-Type Mediterranean Ecosystem and its Contribution to the Local Water Balance - Kurz-Besson, Cathy; Otieno, Dennis; Lobo do Vale, Raquel; Siegwolf, Rolf; Schmidt, Markus; Herd, Alastair; Nogueira, Carla; David, Teresa Soares; David, Jorge Soares; Tenhunen, John; Pereira, João Santos; Chaves, Manuela (Plant and Soil, 2006)
The aim of this study was to identify the sources and depth of water uptake by 15-years old Quercus suber L. trees in southern Portugal under a Mediterranean climate, measuring d 18 O and dD in the soil–plantatmosphere continuum. Evidence for hydraulic lift was substantiated by the daily ﬂuctuations observed in Ys at 0.4 and 1 m depth and supported by similar d 18 O values found in tree xylem sap, soil water in the rhizosphere and groundwater. From 0.25 m down to a depth of 1 m, dD trends diﬀered according to vegetation type, showing a more depleted value in soil water collected under the evergreen trees ()47&) than under dead grasses ()35&). The hypothesis of a fractionation process occurring in the soil due to diﬀusion of water vapour in the dry soil is proposed to explain the more depleted soil dD signature observed under trees. Hydraulically lifted water was estimated to account for 17–81% of the water used during the following day by tree transpiration at the peak of the drought season, i.e., 0.1–14 L tree )1 day )1 . Signiﬁ- cant relationships found between xylem sap isotopic composition and leaf water potential in early September emphasized the positive impact of the redistribution of groundwater in the rhizosphere on tree water status.
Keywords: d 18 o; hydraulic lift; Quercus suber; root biomass; soil dd fractionation; soil water potential